Developing a non-invasive diagnostic model for pediatric Crohn’s disease using RNA-seq analysis - He, Bin; Wang, Fang; Shu, Junhua; Cheng, Ying; Zhou, Xiaoqing; Huang, Tao (Frontiers in Genetics, 2023)
Pediatric Crohn's disease is a chronic inflammatory condition that affects the digestive system in children and adolescents. It is characterized by symptoms such as abdominal pain, diarrhea, weight loss, and malnutrition, and can also cause complications like growth delays and delayed puberty. However, diagnosing pediatric Crohn's disease can be difficult, especially when it comes to non-invasive methods. In this study, we developed a diagnostic model using RNA-seq to analyze gene expression in ileal biopsy samples from children with Crohn's disease and non-pediatric Crohn's controls. Our results showed that pediatric Crohn's disease is associated with altered expression of genes involved in immune response, inflammation, and tissue repair. We validated our findings using two independent datasets from the Gene Expression Omnibus (GEO) database, as well as through our own collection of whole blood samples, and found that our model had a high accuracy rate. These findings suggest the possibility of non-invasive diagnosis for pediatric Crohn's disease and may inform the development of targeted therapies for this condition.